2020
DOI: 10.3390/ijerph17238726
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Predictors of the Risk of Postpartum Depressive Disorder: Results of a Case-Control Study

Abstract: Background: The study aimed at the identification of the risk factors present during delivery, which might be present in prophylactic programs concerning postpartum mood disorders. Material and Method: This was a retrospective comparative study. The study material included data retrieved from the medical records of patients hospitalized in the Teaching Department of Gynecology and Obstetrics of Professor Orłowski Hospital in Warsaw, in the years 2010–2017. The EPDS data of 604 patients were analyzed. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
0
12
0
5
Order By: Relevance
“…The majority of studies have focused on the presence of previous affective episodes as risk factors for MB, while the finding that the presence of anxiety disorders is a risk factors for MB is rather new, although the impact of anxiety disorders on the onset of PPD had already been reported ( 41 ). It may be that women with anxiety disorders may perceive as more stressful the changes in their lifestyle behaviors imposed by the motherhood and feel less ready to take over the new role of mother ( 42 ). It has to be noted that, when assessing EPDS subscales immediately after the delivery, the levels of anxiety symptoms are notably higher compared to the levels of affective symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have focused on the presence of previous affective episodes as risk factors for MB, while the finding that the presence of anxiety disorders is a risk factors for MB is rather new, although the impact of anxiety disorders on the onset of PPD had already been reported ( 41 ). It may be that women with anxiety disorders may perceive as more stressful the changes in their lifestyle behaviors imposed by the motherhood and feel less ready to take over the new role of mother ( 42 ). It has to be noted that, when assessing EPDS subscales immediately after the delivery, the levels of anxiety symptoms are notably higher compared to the levels of affective symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Mulheres que foram submetidas a cesarianas, além daquelas que passaram por partos com utilização de fórceps, espátulas ou ventosas foram mais suscetíveis a desenvolver baby blues do que mulheres que passaram por parto natural. 15 Além disso, apesar da analgesia peridural auxiliar na diminuição da dor durante o parto, pode estar diretamente correlacionada à liberação de cortisol, no desenvolvimento de sintomatologia depressiva e do aparecimento do baby blues. 18 Outro fator de risco para o baby blues está relacionado à internação da mulher para o parto.…”
Section: Discussão O Baby Blues Seus Sinais E Sintomas E Seus Fatores...unclassified
“…Tal fato se explica pela ansiedade materna vivenciada durante a hospitalização e o sentimento de impotência de reverter tal situação do recém-nascido. 15 Gravidezes de alto risco e partos prematuros também podem aumentar o sofrimen-to psíquico da mulher. Estudos demonstraram que a perda sanguínea acima de 400ml durante o parto aumentou a ansiedade, o medo e o estresse da mulher.…”
Section: Discussão O Baby Blues Seus Sinais E Sintomas E Seus Fatores...unclassified
See 1 more Smart Citation
“…The association between the mode of delivery and postpartum depression remains unclear. Whereas some studies reported elevated levels of postpartum depressive symptoms amongst women who underwent operative birth or had perinatal factors such as significant blood loss or longer duration of stage II or III of labor [ 10 ]; other studies, including systematic reviews, found no significant association [ 11 , 12 ]. However, subjective perception of the birth experience and level of birth satisfaction might be more important risk factors of postpartum depression than the objective mode of delivery.…”
Section: Introductionmentioning
confidence: 99%